Anti-inflammatory activity and polyphenolic profile of the hydroalcoholic seed extract of Eugenia leitonii, an unexplored Brazilian native fruit. (October 2016) - Lazarini, Josy Goldoni; Franchin, Marcelo; Infante, Juliana; Paschoal, Jonas Augusto Rizzato; Freires, Irlan Almeida; de Alencar, Severino Matias; Rosalen, Pedro Luiz
Highlights: This study demonstrates the anti-inflammatory activity, mechanisms of action and chemical profile of Eugenia leitonii . Anti-inflammatory activity was observed in vitro and in vivo. E.   leitonii extract showed high concentrations of phenolic compounds. There was a predominance of anthocyanins, flavonols and ellagitannins in the extract. It could be a promising source of molecules with anti-inflammatory potential. Abstract: This study determined the anti-inflammatory activity, mechanisms of action, and polyphenolic profile of Eugenia leitonii seed extract. The total phenolic content of the hydroethanolic extract from E. leitonii seeds (ESEL) was measured, and its phenolic compounds were identified by LC-MS/MS. The ESEL was submitted to in vitro (RAW264.7) and in vivo assays on neutrophil migration; expression of P-selectin and ICAM-1; release of TNF-α, IL-1β, and CXCL2/MIP-2; NF-κB activation; and carrageenan-induced paw oedema. ESEL yielded total phenolic content of 158.74 ± 3.5 mg GAE/g, with the presence of flavonols, anthocyanins and ellagitannins. ESEL significantly reduced neutrophil migration; decreased the expression of P-selectin and ICAM-1; decreased the release of TNF-α and CXCL2/MIP-2, as well as NF-kB activation and paw oedema in mice. Thus, this extract showed to be a promising source of bioactive compounds with anti-inflammatory potential by inhibiting neutrophil migration through a decrease in the release of TNF-α and CXCL2/MIP-2 (NF-κB pathway) in macrophages.